Metal-free sustainable synthesis of oximes and hydrazones from benzyl alcohol and benzylamine - Devgunde, Rupali B.; Rupanawar, Bapurao D.; Rupnavar, Prasad B.; Waghmode, Suresh B. (RSC Advances, 2026)
Herein, we report a one-pot synthesis of oximes and hydrazones via oxidative coupling of alcohols and amines with hydroxylamine hydrochloride and hydrazine, mediated by N-bromosuccinimide (NBS) and phenyliodine(iii) diacetate (PIDA), respectively. NBS mediates the benzyl alcohol oxidation, followed by coupling with hydroxylamine hydrochloride, as well as hydrazines, leading to the formation of oximes and hydrazones, respectively. Additionally, PIDA oxidizes benzylamine to the corresponding intermediate imine, which then reacts with hydroxylamine hydrochloride and hydrazine to form oximes and hydrazones, respectively. We have also demonstrated the effectiveness of this methodology through a gram-scale reaction and synthetic transformation.